The Effect of Changes in Postural Position Angle Degree on Central Venous Pressure Measurement - Lesmana, Hendy; Ose, Maria Imaculata; Zulfia, Rahmatuz; Tobing, Kurniaty Ika Sari (Indonesian Journal of Medicine, 2019)
Background: Central venous pressure is often used in intensive care, especially in patients who experience impaired fluid balance, heart failure, evaluation of therapeutic response and media for therapy or hypertonic fluid. The patient's hemodynamic condition during treatment in the intensive care unit (ICU) is constantly changing (unstable), therefore, serial monitoring of central venous pressure is needed and the patient's position must be constant. Changing the position of the patient in a place is sometimes something that cannot be avoided when the patient is in intensive room. This study aimed to examine the effect of changing the position of patients in bed at 00, 150, 300, and 450 on central venous pressure (CVP) values.  Subjects and Method: This was quasi-experimental study, using a post test without control group with repeated measures. This study was conducted in the ICU/ICCU Room at Tarakan Hospital, North Kalimantan, from May to June 2019. A total of 30 patients was selected by accidental sampling. The dependent variable was central venous pressure. The independent variable was the position of the patient when a central venous pressure examination was carried out, with the degree of positions which were 00, 150, 300, and 450. The data was obtained from observation sheet. CVP was measured by water manometer. The data were analyzed by Anova.Results: The lowest mean CVP was achieved at 0º (Mean=15.13; SD= 5.79). The highest mean CVP was achieved at 45º (Mean=18.18; SD=5.35). The different mean between 0º and 45º was statistically significant (p=0.001). The mean CVD at 15º was mean=16.35; SD=5.73. The mean CVD at 30º was mean=17.07; SD=5.42). The different mean between 15º and 30º was statistically significant (p=0.047).  Conclusion: The best position for perform central venous pressure is 45o.Keywords:  central vein pressure, intensive care, patient positionCorrespondence: Hendy Lesmana. Nursing Department, Faculty of Health, Universitas Borneo Tarakan. Email: damayanti.titha@gmail.com.Indonesian Journal of Medicine (2019), 4(3): 192-200https://doi.org/10.26911/theijmed.2019.04.03.01